Análisis del procéso documental para la exportación de banano para la asociación de productores bananeros orgánicos Agroverde, provincia de El Oro - Zambrano Orellana, Katherine Elvira (2015)
This project focuses on finding solutions that exist in different companies in the commercial field worldwide, one of the issues the documentary process they made to market your product. It is focused on finding possible needs with agricultural associations today. This document fundamental standards required academic level which are scientific articles (papers) that must be related to the problem and give a contribution to its analysis and subsequent solution is found.